The agency costs in university institutions: an analytical model for its evaluation - Rabossi, Marcelo (Education Policy Analysis Archives, 2014)
In a contractual situation, adverse selection problems and moral hazard risks are commonly seen as organizational or behavioral anomalies that impede that a transaction of goods or services develops efficiently. Generated by informational asymmetries, high monitoring costs, and different preferences between the employer and employees, these agency costs impede institutions from attempting to reach the frontiers of their productive capacity. Universities have been criticized for such pathologies, which in the end increase their costs of production. We propose an analytical model to evaluate whether or not universities are, and if so, then to what degree, attentive to mitigating agency costs. Using the New Institutional Economics (NIE) as the theoretical framework, we suggest to explore academic internal labor markets through explicit (written rules and norms) and implicit contracts (organizational climate). The main contribution of this work lies in proposing to study the working conditions of faculty members with the logic of an economic explanation, deviating from the more traditional sociological and psychological points of view that are generally used in the analysis of faculty life.